2015
DOI: 10.1002/micr.22478
|View full text |Cite
|
Sign up to set email alerts
|

Supramicrosurgical lymphatic‐venous anastomosis for postsurgical subcutaneous lymphocele treatment

Abstract: Postsurgical subcutaneous lymphocele is caused by accidental lesion of a lymphatic vessel that keeps on flowing lymph under the scar. Traditional treatments include aspiration and compression, with probable recurrence, and sclerotherapy which destroys both lymphatic cyst and vessel, creating risk of lymphedema. We describe the case of a postsurgical subcutaneous lymphocele of the left leg that was treated by supramicrosurgical lympatic-venous anastomosis. A single anastomosis was performed end-to-end, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…The lymphatic function of the limbs was also evaluated by preoperative indocyanine green (ICG) lymphography, according to a method that we routinely employ for lymphedema and lymphocele study, and widely reported in literature (Gentileschi et al, ; Yamamoto et al, ); 0.2 ml of ICG (Verde Indocianina Pulsion, Pulsion Medical Systems AG Sthalgruberring 28 D‐81829 Monaco, Germania) were injected intradermally at the first web space of the foot and at the lateral border of the Achilles tendon at the level of the external malleolus. After injection, dynamic lymphatic vessels images were obtained by an infrared camera system (Photodynamic Eye; Hamamatsu Photonics K.K., Hamamatsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The lymphatic function of the limbs was also evaluated by preoperative indocyanine green (ICG) lymphography, according to a method that we routinely employ for lymphedema and lymphocele study, and widely reported in literature (Gentileschi et al, ; Yamamoto et al, ); 0.2 ml of ICG (Verde Indocianina Pulsion, Pulsion Medical Systems AG Sthalgruberring 28 D‐81829 Monaco, Germania) were injected intradermally at the first web space of the foot and at the lateral border of the Achilles tendon at the level of the external malleolus. After injection, dynamic lymphatic vessels images were obtained by an infrared camera system (Photodynamic Eye; Hamamatsu Photonics K.K., Hamamatsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…6,16 Inguinal defect was in 20 cases a wide subcutaneous defect following extended groin dissection with 3 of them including also an inguinal skin resection because of proximity of pathologic nodes, and in three cases was caused by the removal of a big lymphocele, developed after groin dissection. 17 Age, height, weight, and body mass index (BMI) of patients were recorded. Every patient had undergone preoperative high-resolution contrast-enhanced total body computed tomography (CT) scan, with focus at the level of genitalia and groins for cancer staging.…”
Section: Methodsmentioning
confidence: 99%
“…The preoperative lymphatic mapping of patients was achieved at the moment of ICG lymphography on the day before surgery with a painless injections technique (Visconti, Albanese, & Salgarello, ). The exam was accomplished according to a method widely reported in literature (Yamamoto, Yamamoto, et al, ), routinely employed for Lymphedema and Lymphocele preoperative study (Gentileschi, Servillo, & Salgarello, ; Gentileschi, Servillo, Ferrandina, & Salgarello, ). 0.1 mL of ICG (Verde Indocianina Pulsion, Pulsion Medical Systems AG Sthalgruberring 28D‐81829 Monaco, Germany) was injected intradermal at the second web space of the hand and at the ulnar border of the palmaris longus tendon at the level of the wrist, in both the upper limbs.…”
Section: Lymphatic Mappingmentioning
confidence: 99%
“…The preoperative lymphatic mapping of patients was achieved at the moment of ICG lymphography on the day before surgery with a painless injections technique (Visconti, Albanese, & Salgarello, 2017). The exam was accomplished according to a method widely reported in literature , routinely employed for Lymphedema and Lymphocele preoperative study (Gentileschi, Servillo, & Salgarello, 2015;Gentileschi, Servillo, Ferrandina, & Salgarello, 2017). The tendon of the palmaris longus muscle, at the level of the wrist, the midpoint of the cubital fossa, and the insertion of the anterior axillary pillar on the arm.…”
Section: Ym P H a Ti C M A P P I Ngmentioning
confidence: 99%